The Effect of Social Support on Mental Health in Chinese Adolescents During the Outbreak of COVID-19 - Qi, Meng; Zhou, Shuang-Jiang; Guo, Zhao-Chang; Zhang, Li-Gang; Min, Hong-Jie; Li, Xiao-Min; Chen, Jing-Xu (Journal of adolescent health, 2020)
The coronavirus disease 2019 (COVID-19) outbreak impacts physical and mental health. The purpose of this study was to explore the association between the levels of social support and mental health among Chinese adolescents during the outbreak. A total of 7,202 adolescents aged 14–18 years completed online survceys from March 8 to 15, 2020, in China. Researchers assessed the associations between depression symptoms (Patient Health Questionnaire-9), anxiety symptoms (Chinese version of the 7-item Generalized Anxiety Disorder scale), and social support (Social Support Rate Scale). COVID-19 exposure was associated with a higher prevalence of depression symptoms (odds ratio [OR] = 1.38, 95% confidence interval [CI]: 1.14–1.66) and anxiety symptoms (OR = 1.26, 95% CI: 1.04–1.52). Only 24.6% of adolescents reported high levels of social support. Most adolescents (70%) reported medium levels of support, and 5.4% reported low support. Low support was associated with higher prevalence of depression (OR = 4.24, 95% CI: 3.38–5.33) and anxiety symptoms (OR = 3.18, 95% CI: 2.54–3.98), while controlling for gender, grade, living situation, and COVID-19 exposure; similarly, medium support was associated with higher prevalence of depression (OR = 2.79, 95% CI: 2.48–3.15) and anxiety (OR = 2.19, 95% CI: 1.94–2.48) symptoms. This study indicates there is a higher prevalence of mental health problems among adolescents with medium and low levels of social support in China during the outbreak of COVID-19.